2013
DOI: 10.2337/db12-0771
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropathic Diabetic Foot Ulcer Microbiome Is Associated With Clinical Factors

Abstract: Nonhealing diabetic foot ulcers (DFUs) are a common and costly complication of diabetes. Microbial burden, or “bioburden,” is believed to underlie delayed healing, although little is known of those clinical factors that may influence microbial load, diversity, and/or pathogenicity. We profiled the microbiomes of neuropathic nonischemic DFUs without clinical evidence of infection in 52 individuals using high-throughput sequencing of the bacterial 16S ribosomal RNA gene. Comparatively, wound cultures, the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
334
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(356 citation statements)
references
References 30 publications
18
334
2
2
Order By: Relevance
“…The role of the skin microbiome in UC was explored in 10 different studies, Table 1 37, 38, 39, 40, 41, 42, 43, 44, 45, 46. Current research into UC microbiome, comprises larger, longitudinal studies, compared to those in PV and HS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of the skin microbiome in UC was explored in 10 different studies, Table 1 37, 38, 39, 40, 41, 42, 43, 44, 45, 46. Current research into UC microbiome, comprises larger, longitudinal studies, compared to those in PV and HS.…”
Section: Resultsmentioning
confidence: 99%
“…The skin mycobiota of diabetic foot ulcers was longitudinally assessed and was observed to be highly heterogeneous over time and between subjects while the diversity increased upon antibiotic treatment 45. There have been similar efforts to reveal correlations between patient metadata, treatment and/or clinical outcomes and the cutaneous microbiome in studies investigating the microbiota in UC 38, 42, 43, 44, 46. Overall, the most common found genus in these studies was Staphylococcus , with Staphylococcus aureus the most common species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional bacterial culture is the most widely available tool for the diagnosis of bacterial infection, but has been shown consistently to underestimate the complexity of wound bacterial burden as revealed by DNA-based molecular methods. [6][7][8][9][10] Bacteria in chronic wounds grow in biofilms, which include many anaerobes and other species not identified by cultivation-based methods. 7,[10][11][12] This complexity of the microbial flora in chronic wounds may explain the lack of improved clinical outcomes observed in many studies of antimicrobial use targeting bacteria identified by cultivation-based methods.…”
Section: Introductionmentioning
confidence: 99%